MEDOWO SEBAGAI KOTA MAJAPAHIT (DESKRIPSI BERDASARKAN SUMBER SEJARAH DAN ARKEOLOGI) - Inggrid H.E. Pojoh (Berkala Arkeologi, 1994)
Medowo is the name of a hamlet located in the delta of the Brantas River, approximately 5 kilometers east of the Brantas River branching into the Mas River (Surabaya) and the Porong River. Research in Medowo conducted by the Yogyakarta Archeology Center in 1986 showed that many village indicators were found at the ground surface as well as archaeological sites. Simply put, this site shows the characteristics of a settlement site from the Hindu-Buddhist period. Perhaps the only inscription source containing a toponym for Medowo is the Jiwu III inscription, which dates from the Late Majapahit era. This inscription was published in the same year as the Jiwu I and II inscriptions, namely in the year Saka 1408 or AD 1486. If it is true that the place called Majapahit by the Chinese news is a place at the mouth of the Brantas River, in this case Medowo, it is very likely a form. The settlement that existed at that time in Medowo was not a simple settlement.